Al2O3-MgO Supported Ni, Mo, and NiMo Mixed Phosphidic-Sulphidic Phase for Hydrotreating of Stearic and Oleic Acids Into Green Diesel - Puello-Polo, Esneyder; Arias, Dana; Márquez, Edgar (Frontiers in Chemistry, 2022)
The effect of the sulfur and metal-type content of MoP-S/γ-Al2O3-MgO, NiMoP-S/γ-Al2O3-MgO, and NiP-S/γ-Al2O3-MgO phosphide on hydroprocessing (HDO, HDCx-HDCn, HCK, HYD, and HYG) of fatty acids was studied. The catalysts were characterized by XRF, XRD, textural properties, XPS, Raman, Py-TPD, and EDS elemental mapping. The chemical analyses by X-ray fluorescence (XRF), EDS elemental mapping, and CHNS-O elemental analysis showed stoichiometric values Al/Mg = 38–40, Mo:Ni:P ∼ 1, and S ≤ 4.5 wt % (this value means that the molar ratio Mo:S ∼ 1.0:1.6, i.e., MoS2); also EDS elemental mapping confirmed the presence of Mo, Ni, Al, O, P, Mg, and S with good distribution on Al2O3-MgO. The impregnation of metals leads to a decrease in the surface area and pore volume as follows NiMoP-S/γ-Al2O3-MgO < MoP-S/γ-Al2O3-MgO < NiP-S/γ-Al2O3-MgO < Al2O3-MgO < Al2O3 (unimodal pore size distribution), propitiating a pseudo bimodal pore size distribution with Dp-BJH between ∼5–7 nm and 11.8–14.2 nm for the presence of MgO. XRD confirmed differences between metallic phosphates and phosphides, and XPS confirmed the presence at the surface of Moδ+(0 < δ+ < 2), Mo4+, Mo6+, Niδ+(0 < δ+ < 2), Ni2+, S2−, SO42−, Pδ+, and P5+ species. Raman revealed the presence of MoS2 only in MoP-S/γ-Al2O3-MgO and NiMoP-S/γ-Al2O3-MgO, while the NiMoP-S/γ-Al2O3-MgO catalyst had a more significant number of Brønsted and Lewis sites, although the increasing temperature decreased the Lewis sites. MoP-S/γ-Al2O3-MgO was more active at HDO showing the highest production rate for octadecane of 53 mol/(gcat·h), whereas NiP-S/γ-Al2O3-MgO was more active at HDCx-HDCn [45 mol/(gcat·h)] and HCK [6 mol/(gcat·h)]; meanwhile, NiMoP-S/γ-Al2O3-MgO had a mix of HDO [47 mol/(gcat·h)] and HDCx-HDCn [41 mol/(gcat·h)]. This showed production towards octadecane, heptadecane, and light hydrocarbons, meaning that the fatty acids were deoxygenated through bifunctional sites for hydrogenation (HYD) and hydrogenolysis (HYG) as follows: MoP-S/γ-Al2O3-MgO (K1 = 0.08 and K2 = 0.03 L/mol) < NiMoP-S/γ-Al2O3-MgO (K1 = 0.25 and K2 = 0.45 L/mol) < NiP-S/γ-Al2O3-MgO (K1 = 2.5 and K2 = 6.5 L/mol). For this reason, we considered that phosphide acts as a structural promoter with sulfur on its surface as a “mixed phosphidic-sulphidic species”, allowing the largest generation of heptadecane and octadecane by the presence of BRIM sites for HYD and CUS sites for HYG.